Demystifying Tuition? A Content Analysis of the Information Quality of Public College and University Websites. (August 2019) - Davis, Laura A.; Wolniak, Gregory C.; George, Casey E.; Nelson, Glen R.
Colleges and universities increasingly rely on their websites to recruit students and convey information about tuition and costs of attendance. Given evidence of growing complexity in institutional tuition policies and cost-setting practices, the study examined how institutions' websites present financial information to the public. Through content analysis of website data from 50 public colleges and universities, researchers sought to characterize patterns in the scope and quality of tuition information on institutional websites and to understand how these patterns might influence individuals' conceptions of tuition and costs. The findings point to variation in informational quality across dimensions ranging from clarity of language use and terminology, to consistency and coherence of visual displays, which accompany navigational challenges stemming from information fragmentation and discontinuity across pages. Implications for research and improved institutional practice are discussed.